Pengaruh Motivasi, Budaya dan Kemampuan terhadap Kepuasan Kerja dan Kinerja Guru SMP Negeri di Kota Makassar - Megawati Megawati (Jurnal Dirosah Islamiyah, 2021)
This research is conducted in order to: analyze the influence of Motivation, Culture, Ability, toward Work Satisfaction and Teacher’s Performance in Senior high School State in Makassar South Sulawesi to obtain of more deep influence of culture, Motivation, Ability toward Worked Satisfaction and teacher’s Performance in yunior high school in Makassar. Data is analyzed constructively by using the technique analyze the SEM (Structural Equation Modeling) with AMOS 18 program (Analyze of Moment Structural). Research location is the teachers of senior high school in Makassar respondent of research the teaher in Senior highg School. As sample of the research is 120 respondents. Result of the research indicate that there are positive direct influence and significant from Culture, otivation, Ability toward Worked Satisfaction and Teacher’s Performance in Senior High School in Makassar, there are positive direct influence and significant from factor Motivation toward worked satisfaction and Teacher’s Performance, in Senior high school Makassar South Sulawesi province.